Initiating Change of People With Criminal Justice Involvement Through Participation in a Drama Project: An Exploratory Study - Mundt, Adrian P.; Marín, Pamela; Gabrysch, Caroline; Sepúlveda, Carolina; Roumeau, Jacqueline; Heritage, Paul (Frontiers in Psychiatry, 2019)
Introduction Innovative and interdisciplinary approaches are needed to improve mental health and psychosocial outcomes of people with criminal justice involvement and their families. Aim of the study was to assess effects of the participation in a theatre project on the mental health problems of people with criminal justice involvement and relatives. Methods We conducted structured diagnostic interviews and in-depth qualitative interviews with five participants performing Shakespeare’s Richard III in Chile. Three participants had been imprisoned prior to the project and two were the parents of a person who died in a prison fire. Qualitative interviews followed a topic guide. Data were transcribed and a 6-phase approach for thematic analysis of the data was used. Results Substance use disorder or major depression were identified in all the participants. Participation in the theatre project was experienced by the respondents as having a positive effect on the mental health conditions. The research registered the positive experiences of role identification, emotional expression, commitment with group processes, improved skills to socially interact, to be heard by the general public and society, and positive perceptions of the audience (including relatives). Discussion The study raises the possibility that there may be improvements of depression and substance use problems through the participation of people with criminal justice involvement in a drama project. Wider scale research is recommended on the possible effects. The approach may be an alternative to psychotherapy and medication for some individuals.